2017
DOI: 10.1158/1078-0432.ccr-17-2169
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Phase II Trial of Adjuvant Galinpepimut-S, WT-1 Analogue Peptide Vaccine, After Multimodality Therapy for Patients with Malignant Pleural Mesothelioma

Abstract: Purpose Determine the 1-year progression-free survival (PFS) among patients with malignant pleural mesothelioma (MPM) receiving the WT1 peptide vaccine galinpepimut-S after multimodality therapy vs those receiving control adjuvants. Patients and Methods This double-blind, controlled, two center phase II trial randomized MPM patients after surgery and another treatment modality to galinpepimut-S with GM-CSF and Montanide or GM-CSF and Montanide alone. An improvement in 1-year PFS from 50% to 70% was the prede… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 23 publications
1
29
0
7
Order By: Relevance
“…In the adjuvant space, interventions with vaccines may have promise. Galinpepimut-S Wilms tumor 1 vaccine was randomized against placebo in a double-blind trial 31 ; when administered after macroscopic complete resection, the vaccine demonstrated superiority over control. The median progressionfree survival (PFS) was 7.4 months versus 10.1 months, and the median overall survival (OS) was 18.3 months versus 22.8 months in the control and vaccine arms, respectively.…”
Section: Background Therapies In Early-stage Mpmmentioning
confidence: 99%
“…In the adjuvant space, interventions with vaccines may have promise. Galinpepimut-S Wilms tumor 1 vaccine was randomized against placebo in a double-blind trial 31 ; when administered after macroscopic complete resection, the vaccine demonstrated superiority over control. The median progressionfree survival (PFS) was 7.4 months versus 10.1 months, and the median overall survival (OS) was 18.3 months versus 22.8 months in the control and vaccine arms, respectively.…”
Section: Background Therapies In Early-stage Mpmmentioning
confidence: 99%
“…Although the control arm was closed early due to a prespecified futility analysis and the trial was not powered for comparison between the two arms, the median PFS (10.1 vs. 7.4 months) and median OS (22.8 vs. 18.3 months) favored patients who received the WT-1 vaccine. 142 Dendritic cell-based immunotherapy involves pulsing autologous harvested dendritic cells ex vivo with tumor lysate followed by dendritic cell vaccination to generate a tumor-specific immune response. Hegmans et al demonstrated safety, feasibility, and induction of an antitumor immunological response in MPM patients treated with dendritic cell vaccine and chemotherapy.…”
Section: Immunotherapymentioning
confidence: 99%
“…The WT1 protein is highly immunogenic (29). Immunotherapies targeting WT1 have been developed in a number of countries as novel, promising therapeutic strategies for various types of cancer such as leukemia, glioblastoma and pancreatic cancer (30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%